Analisis Implementasi Strategi Pengembangan Karakter Disiplin Melalui Pembelajaran Pendidikan Pancasila pada Siswa Kelas 4 SDN 192 Ciburuy - Fatimah, Siti; Komariah, Komariah; Furnamasari, Yayang Furi (Indo-MathEdu Intellectuals Journal, 2024)
This study describes the implementation of disciplinary character development strategies through Pancasila education learning and its impact on grade 4 students, obstacles and solutions, and student responses regarding the implementation. The research method used is qualitative with a descriptive approach. Data were collected through observation, interviews, questionnaires, and documentation. The data analysis technique uses Miles & Huberman analysis which consists of data reduction, data presentation and conclusion drawing. The results showed that the implementation of disciplinary character development strategies through Pancasila education learning was carried out through habituation, exemplary, advice, and rules at the beginning to end of learning activities which had a good impact on student discipline. The obstacles felt are related to infrastructure, lack of parental contribution, difficulty in choosing words in delivering advice and lack of student awareness. Solutions include adjusting teaching techniques, communicating with parents, delivering advice with seduction, stories or fairy tales, and providing understanding to students. Student responses related to the implementation are that disciplinary character development strategies can be implemented in Pancasila education learning through habituation, exemplary, advice, and rules